2016
DOI: 10.1074/jbc.m115.686360
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Translocator Protein (TSPO) Function Is Not Essential for Heme Biosynthesis

Abstract: Function of the mammalian translocator protein (TSPO; previously known as the peripheral benzodiazepine receptor) remains unclear because its presumed role in steroidogenesis and mitochondrial permeability transition established using pharmacological methods has been refuted in recent genetic studies. Protoporphyrin IX (PPIX) is considered a conserved endogenous ligand for TSPO. In bacteria, TSPO was identified to regulate tetrapyrrole metabolism and chemical catalysis of PPIX in the presence of light, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 61 publications
(67 reference statements)
2
48
1
Order By: Relevance
“…The link between TSPO and mitochondrial energy homeostasis is inconsistent and perhaps dependent on cell type. Studies have reported that TSPO deletion results in a decreased oxygen consumption rate (OCR) in microglia[4] and fibroblasts[40], but no change in OCR was observed in hepatocytes[13] and Leydig cells[41]. An increase in mitochondrial fatty acid oxidation was observed in steroidogenic cells and tissues[41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between TSPO and mitochondrial energy homeostasis is inconsistent and perhaps dependent on cell type. Studies have reported that TSPO deletion results in a decreased oxygen consumption rate (OCR) in microglia[4] and fibroblasts[40], but no change in OCR was observed in hepatocytes[13] and Leydig cells[41]. An increase in mitochondrial fatty acid oxidation was observed in steroidogenic cells and tissues[41].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in mitochondrial fatty acid oxidation was observed in steroidogenic cells and tissues[41]. But TSPO is not required for steroid hormone biosynthesis as previously suggested[4,5,12,17,40]. The loss of TSPO in experimental autoimmune encephalomyelitis (EAE) mice, an animal model of multiple sclerosis (MS), caused mild astrogliosis and less EAE clinical scoring[42].…”
Section: Discussionmentioning
confidence: 99%
“…7072 The seemingly definitive TSPO knockout experiments have also led to conflicting results. 31,61,62 However, one consistent finding from knockout experiments appears to be altered mitochondrial energy metabolism, including lower oxygen consumption, membrane potential, and ATP levels. 40,41,61,73 This observation fits with the additional finding of an increased level of fatty acid oxidation in the absence of TSPO, 74 but how these observations relate to another emerging common theme, sensing or responding to stress, and how they may be associated with oxygen radical production and regulatory phenomena, remains to be determined.…”
Section: Functional Puzzle Of Tspomentioning
confidence: 99%
“…2931 Several other TSPO −/− mouse constructs have yielded conflicting reports regarding lethality and other characteristics. 31,41,42,58,61 These differences have been discussed in detail, 39,62,75 clarifying some of the complex issues involved in the methodology that may explain the discrepancies. Recent results from conditional, cell-targeted TSPO deletion show altered development and hormone-driven steroid synthesis, 62 in keeping with the role of TSPO as a stress response player in steroid metabolism.…”
Section: What Is the Role Of Tspo In Cholesterol Transport Or Translomentioning
confidence: 99%
See 1 more Smart Citation